OBSERVASI PENGKAJIAN KELENGKAPAN RESEP OBAT BATUK SECARA ADMINISTRATIF DAN FARMASETIK PADA PUSKESMAS CILAMAYA DI KABUPATEN KARAWANG - Caroline Noer Asy'ary (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
An incomplete prescription has the potential to be one of the causes of medication errors. This incident can be avoided by conducting prescription screening by pharmacists which includes a review of administrative and pharmaceutical aspects. The purpose of this study was to determine the administrative and pharmaceutical completeness of prescriptions for the period January – May 2021 at the Cilamaya Health Center in Karawang Regency. The research method is descriptive quantitative with retrospective data collection. The sampling technique was simple random sampling, and 428 prescription sheets were obtained that met the inclusion criteria. The results showed that the administrative completeness of the prescription consisted of: patient's name 100%, patient age 96%, gender 0%, weight 96%, doctor's name 8%, doctor's initials 43%, prescription date 99%, and room of origin. prescription 76%. Meanwhile, pharmaceutically it consists of: 100% dosage form and strength, 96% drug dosage, 99% drug amount, 100% stability and availability, 96% usage rules and 100% compatibility. It can be concluded that based on Permenkes No. 74 of 2016, prescriptions at the Cilamaya Health Center for the period January – May 2021 are not administratively and pharmaceutically complete.